Механізми змін функціонального стану клітин панкреатичних лімфатичних вузлів та парапанкреатичної жирової тканини при експериментальному цукровому діабеті та після введень метформіну - Путілін, Денис Анатолійович; Путилин, Д. А.; Putilin, D. А. (Запорізький державний медичний університет, 2018)
В результаті роботи виявлено комплекс ключових патофізіологічних і функціональних змін в клітинах ПЛВ і ПЖТ в умовах ЕСІЦД: зміни імунометаболізму лімфоцитів; порушення формування периферичної імунологічної толерантності; активація ПРР вродженої імунної системи на лімфоцитах ПЛВ і адипоцитах ПЖТ; зміни розподілу ефекторних Т-клітин в ПЛВ; посилення прозапальної сигналізації в ПЖТ на фоні зменшення рівня мРНК Foxp3. Вперше встановлено, що гіперглікемія викликає транскрипційну індукцію генів транспортерів глюкози Glut 1 та протеїнкінази mTOR в імунних клітинах ПЛВ, що є важливим тригером їх диференціювання в ефекторні прозапальні субпопуляції Th1 і Th17. Експериментально доведено активацію компонентів вродженої імунної системи при розвитку ЦД і зростання кількості TLR2+-, TLR4+, NOD2+- і RIGI+-лімфоцитів у ПЛВ щурів, забезпечуючи нове розуміння молекулярного патогенезу ЦД 1-го типу. Розширені наукові поняття щодо ролі жирової тканини у прогресії діабету, обґрунтована доцільність застосування метформіну для корекції імунних порушень, що розвиваються при ЦД. В результате работы выявлено комплекс ключевых патофизиологических и функциональных изменений в клетках ПЛУ и ПЖТ в условиях ЭСИСД: изменения иммунометаболизма лимфоцитов; нарушение формирования периферической иммунологической толерантности; активация ПРР врожденной иммунной системы на лимфоцитах ПЛУ и адипоцитах ПЖТ; изменения распределения эффекторных Т-клеток в ПЛУ; усиление провоспалительной сигнализации в ПЖТ на фоне уменьшения уровня мРНК Foxp3. Впервые установлено, что гипергликемия вызывает транскрипционную индукцию генов транспортеров глюкозы Glut 1 и протеинкиназы mTOR в иммунных клетках ПЛУ, что является важным триггером их дифференцировки в эффекторные провоспалительные субпопуляции Th1 и Th17. Экспериментально доказано активацию компонентов врожденной иммунной системы при развитии СД и рост количества TLR2+-, TLR4+-, NOD2+- і RIGI+-лимфоцитов в ПЛУ крыс, обеспечивая новое понимание молекулярного патогенеза СД 1-го типа. Дополнены научные понятия о роли жировой ткани в прогрессии диабета, обоснована целесообразность применения метформина для коррекции иммунных нарушений, развивающихся при СД. The thesis is devoted to the clarification of the peculiarities of the changes in the functional state of the lymphocytes of the pancreatic lymph nodes and parapancreatic adipose tissue in the experimental diabetes mellitus and after the metformin’s introduction. To achieve the goal, immunofluorescence, immunohistochemical, methods of molecular genetic analysis (RT-PCR), computer analysis of images, statistical methods were used. As a result of the work, a complex of key pathophysiological and functional changes in PLN and PAT cells was found in the ESIDM conditions: changes in the lymphocyte immune metabolism; violation of the formation of peripheral immunological tolerance; PRR activation of the congenital immune system on the lymphocytes of PLN and PAT adipocytes; changes in the distribution of effector T cells in the PLN; increase of pro-inflammatory signaling in the PAT on the background of the mRNA Foxp3 level’s reduction. It was first discovered that metabolic changes developing in conditions of DM can directly affect the immune metabolism of the PLN lymphocytes. It is proved that hyperglycemia causes transcriptional induction of Glut1 glucose transport genes and protein kinase mTOR in PLN cells, does’nt affect the total number of mTOR+-cells in PLN on the 3rd week of the pathological process’s development and leads to their growth on the 5th week of ESIDM. It has been shown that the introduction of metformin to the diabetic rats leads to the increase of mRNA of the gene’s level of AMPK1α in 87 % on the 3rd week and almost in 38 times on the 5th week of the ESIDM development and the suppression of mTOR expression in the PLN (in 3-14.7 times) and Glut 1 (in 2-5,7 times) in PLN. At the same time, the number of mTOR+ -cells decreased in 40 % only in the pulpy bands, in the PLN in the animals with a 5-week ESIDM. For the first time, it has been established that the level of ectopic expression in the PLN cells of the genes- regulators of peripheral immunological tolerance Deaf1 and Aire is reduced in the ESIDM conditions which is accompanied by a decrease of Treg in the PLN. In particular, the Deaf1 expression has decreased in 4.2 times in the rats’ PLN with 3-week ESIDM and in 2.5-times in rats with the 5 week the ESIDM in comparison to the control group. Aire expression has decreased in 2-times in PLN in the rats with 3-week ESIDM and in 50-times in the rats with 5-week ESIDM. It is experimentally proved the activation of the congenital immune system’s components in the DM development and the growth of TLR2+, TLR4+, NOD2+ and RIGI+ lymphocytes in the PLN of rats, providing a new understanding of the molecular pathogenesis of DM type 1. Effects on the growth of the number of cells expressing receptors of congenital immunity depended on the duration of the pathological process – an increase of the ESIDM caused a stronger effect in relation to TLR2+, TLR4+, NOD2+ lymphocytes in the paracortic area and RIGI+ lymphocytes in the pulpy bands of the PLN of the rats. The obtained results indicate, that the ESIDM leads to the significant activation of the congenital immune system, and this, in turn, can significantly affect the level of the adaptive immune response’s activation, the differentiation of the subpopulations of the helper T-cells in the PLN. It has been established that the ESIDM development is accompanied by the changes in the distribution of T-helper cells subpopulations in the PLN of the rats: the total density of Tbet+ lymphocytes in the PLN paracortic area has increased in 56 % -87 %, in the pulpy bands of the PLN, the same indices have increased in 2.3 times and in 68 % in comparison to the control group; the total number of Th17 cells in the paracortic area of the PLN have increased in 2.6 times on the 3rd week and in 46 % on the 5th week of the ESIDM development, in the PLN of pulpy bands – in 65 %-69 %, respectively. This is accompanied by a decrease in the total density of the T-regulatory cells subpopulation in the PLN on the 3rd week of the ESIDM in 25 %-28 %, and on the fifth week – in 50 % only in the pulpy bands, which leads to changes in the distribution of the Treg-lymphocytes separate classes, preferably increases the concentration of the transcription Foxp3 factor in immunopositive cells of the pulpy bands. The scientific concepts are extended due to the role of adipose tissue in the progression of diabetes. It has been determined that in the ESIDM conditions the number of TLR2+ and TLR4+ -adipocytes in parapancreatic fiber increases, which induces proinflammatory signaling in the adipose tissue and increases the mRNA expression of IL1β and IL17A on the background of the transcriptional Foxp3 repression. The expediency of the metformin’s use for the correction of immune disorders developing in the DM is substantiated. For the first time, the metformin’s ability has been shown to influence on the transcriptional activity of the AMPK1α and mTOR genes, to reduce the number of lymphocytes expressing PRR, to alter the distribution of Treg and Th17 cells in the PLN of the diabetic rats.
Механизмы изменений функционального состояния клеток панкреатических лимфатических узлов и парапанкреатической жировой ткани при экспериментальном сахарном диабете и после введений метформина
Mechanisms of the changes in the functional state of the pancreatic lymph nodes’ cells and the parapancreatic adipose tissue in the experimental diabetes mellitus and after the metformin’s introduction
Keywords: цукровий діабет; лімфоцити; адипоцити; метформін; панкреатичні лімфатичні вузли; парапанкреатична жирова тканина; імунометаболізм; сахарный диабет; лимфоциты; адипоциты; метформин; панкреатические лимфатические узлы; парапанкреатическая жировая ткань; иммунометаболизм; diabetes mellitus; lymphocytes; adipocytes; metformin; pancreatic lymph nodes; parapancreatic adipose tissue; immune metabolism